2019
DOI: 10.1017/pab.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

The modern and fossil record of farming behavior

Abstract: Farming is a behavior in which an organism promotes the growth and reproduction of other organisms in or on a substrate as a food source. A number of trace fossils have been suggested to record the occurrence of farming behavior. These include the deep-sea graphoglyptid trace fossils, proposed to be microbial farms on the seafloor, and terrestrial fossil social insect nests thought to represent fungicultural behavior. The presumed farming behavior of graphoglyptids is the basis of the ethological category agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The bioglyphs on the walls of the Clayton Spongeliomorpha are predominately rhombohedral, reflecting the substrate plucking action of chelae during burrow excavation (Ekdale & Gibert ); transverse bioglyphs that may or may not reflect grazing are relatively rare. As recently noted by Hsieh et al (), previous interpretations of gardening or farming behaviours among certain tracemakers, including modern and ancient crustaceans, have yet to be supported by conclusive evidence.…”
Section: Discussionmentioning
confidence: 92%
“…The bioglyphs on the walls of the Clayton Spongeliomorpha are predominately rhombohedral, reflecting the substrate plucking action of chelae during burrow excavation (Ekdale & Gibert ); transverse bioglyphs that may or may not reflect grazing are relatively rare. As recently noted by Hsieh et al (), previous interpretations of gardening or farming behaviours among certain tracemakers, including modern and ancient crustaceans, have yet to be supported by conclusive evidence.…”
Section: Discussionmentioning
confidence: 92%
“…It has also been suggested that Paleodictyon tracemakers, as well as those of other complex graphoglyptid traces, have an agrichnial gardening strategy that involves the culturing of microorganisms within the burrow system as a food source 2 , 32 – 34 . This interpretation has been controversial (see discussion by Hsieh et al 35 ), but if correct, then a larger burrow wall area would provide more space in which to culture bacteria, an advantage in more oligotrophic settings but less advantageous where more food is available and a smaller mesh will suffice.…”
Section: Discussionmentioning
confidence: 99%
“…Biologists and bio-inspired engineers already have a firmly established and fruitful relationship. However, when modern biological techniques and questions are meaningfully applied not only to modern living animals but also to the fossil record, the results are unique and can only aid in finding solutions to bio-inspired engineering concerns [28]. The deep time perspective can help roboticists and paleobiologists to investigate paleobiological questions together that have deep implications for both fields.…”
Section: Understanding Natural Selection To Improve Bio-inspired Robo...mentioning
confidence: 99%